4-(4-Chlorophenyl)-6-hydroxy-5-(2-thienylcarbonyl)-6-(trifluoromethyl)-3,4,5,6-tetrahydropyrimidin-2(1H)-one monohydrate - Mosslemin, Mohammad Hossein (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C(16)H(12)ClF(3)N(2)O(3)S·H(2)O, contains two crystallographically independent organic molecules and two water molecules. The organic species are linked by an intermolecular O—H⋯O hydrogen bond, while the water molecules are connected to them through intermolecular O—H⋯N hydrogen bonds. The thiophene and phenyl rings are oriented at dihedral angles of 62.35 (4) in the first independent molecule and 60.74 (5)° in the second, while the pyrimidine rings adopt twisted conformations in both molecules. Intramolecular N—H⋯F interactions result in the formation of two five-membered rings having envelope conformations. In the crystal structure, further intermolecular O—H⋯O and N—H⋯O hydrogen bonds link the molecules into chains.